Anne Frank. - Davidson, Susanna (b, 2006)
This book tells of the life of Anne Frank, who went into hiding with her family to escape from the Nazis.
Keywords: v; Jews -- Juvenile literature. -- Biography -- Amsterdam -- Netherlands; Holocaust, Jewish (1939-1945) -- Juvenile literature. -- Amsterdam -- Netherlands